Strategic market-oriented profile for micro, small and medium-sized enterprises - Yinet Rodríguez-Sanzo (2025)
The approval of new management forms in Cuba contributes to boosting the business sector with the emergence of Micro, Small and Medium Enterprises (MSMEs). Knowledge of the market is essential for the development of MSMEs to meet customer needs and demands, with maximum utilization of available capabilities. Therefore, the objective of this research is to design a market-oriented strategic profile for MSMEs. A mixed-method approach was used, along with a systematic review in Scopus, SciELO, Google Scholar, SCISPACE, Redalyc, and Dialnet to identify gaps in market orientation models for companies. A market-oriented strategic profile for MSMEs was developed, a user-friendly tool that allows them to work on key aspects to position themselves in the market. It was applied in the SURL SolCaleb MIPYME, where a medium position was identified, based on market participation, brand preference, and customer retention. The results of the research showed that market orientation not only boosts competitiveness but also fosters innovation and adaptability in a constantly changing business environment. The market-oriented strategic profile for MIPYME allows for constant diagnostics to create strategies that improve their positioning and thereby boost the business sector in Cuba.